Innovation, tourism and social networks - Lopes, Romeu (2016)
Innovation is an important source of competitive advantage, being a key research topic. Some authors consider that tourism entrepreneurs typically show scarce business skills and limited innovativeness. Many studies additionally conclude that accommodation businesses are not particularly innovative. This study intends to demonstrate the opposite. Tourism enterprises rarely have research and development (R&D) departments or resources dedicated to systematically enhance innovation. However, the research and knowledge acquisition process takes place in a complex and informal way. Therefore, beyond presenting and classifying some examples of innovation in tourism, this research aims to highlight the role played by social networks as a source of knowledge acquisition, and specifically online reviews as an important basis for innovation of tourism businesses.